A new hypothesis for the pathophysiology of symptomatic adult Chiari malformation Type I. (January 2022) - Labuda, Rick; Nwotchouang, Blaise Simplice Talla; Ibrahimy, Alaaddin; Allen, Philip A.; Oshinski, John N.; Klinge, Petra; Loth, Francis
Abstract: Chiari malformation Type I (CMI) is characterized by herniation of the cerebellar tonsils through the foramen magnum. The pathophysiology of CMI is not well elucidated; however, the prevailing theory focuses on the underdevelopment of the posterior cranial fossa which results in tonsillar herniation. Symptoms are believed to be due to the herniation causing resistance to the natural flow of cerebrospinal fluid (CSF) and exerting a mass effect on nearby neural tissue. However, asymptomatic cases vastly outnumber symptomatic ones and it is not known why some people become symptomatic. Recently, it has been proposed that CMI symptoms are primarily due to instability of either the atlanto-axial (AA) or the atlanto-occipital (AO) joint and the cerebellar tonsils herniate to prevent mechanical pinching. However, only a small percentage of patients exhibit clinical instability and these theories do not account for asymptomatic herniations. We propose that the pathophysiology of adult CMI involves a combination of craniocervical abnormalities which leads to tonsillar herniation and reduced compliance of the cervical spinal canal. Specifically, abnormal AO and/or AA joint morphology leads to chronic cervical instability, often subclinical, in a large portion of CMI patients. This in turn causes overwork of the suboccipital muscles as they try to compensate for the instability. Over time, the repeated, involuntary activation of these muscles leads to mechanical overload of the myodural bridge complex, altering the mechanical properties of the dura it merges with. As a result, the dura becomes stiffer, reducing the overall compliance of the cervical region. This lower compliance, combined with CSF resistance at the same level, leads to intracranial pressure peaks during the cardiac cycle (pulse pressure) that are amplified during activities such as coughing, sneezing, and physical exertion. This increase in pulse pressure reduces the compliance of the cervical subarachnoid space which increases the CSF wave speed in the spinal canal, and further increases pulse pressure in a feedback loop. Finally, the abnormal pressure environment induces greater neural tissue motion and strain, causing microstructural damage to the cerebellum, brainstem, and cervical spinal cord, and leading to symptoms. This hypothesis explains how the combination of craniocervical bony abnormalities, anatomic CSF restriction, and reduced compliance leads to symptoms in adult CMI.